The feasibility and possible benefits of indoor exergames in primary school - Fraile, Luis (2017)
The purpose of this study is to identify the potential contribution of exergames to Primary schoolers, to define what exergames are and to classify them, as well as whether exergames could be an effective tool in physical education lessons from the point of view of students. Can exergames work as a spark to turn on the engine of physical activity practice? Will students acquire or even develop any motor skills by playing exergames that can be transferred into classical physical activities? The study was conducted with eight students of 6th grade in a Primary school in Finland. Students were selected randomly without asking prerequisites or gaming background. During spring season the group participated in seven sessions playing exergames with an Xbox Kinetic console. After the trial sessions, participants were interviewed deeply about their experiences during the trial sessions. Interviews were recorded and transcribed. Answers of the interviews were analyzed following the Phenomenology method of qualitative analysis. The study shows that exergames attracted students through intrinsic motivation to engage an enthusiast and regular participation. Learning games in a physical and psychological safe environment was a determining factor. Besides, discovering new games from the same start point, regarding skills, favored a more homogeneous learning process within the group. The researcher noted as well that balance, rhythm kinesthetic memory and reflexes were other valuable skills developed during the trial sessions.